PEMBERIAN WASIAT WAJIBAH BAGI ANAK LUAR KAWIN DALAM HUKUM ISLAM - Nginggar Ajeng Radindi (Jurnal Hukum Ius Publicum, 2023)
Every marriage definitely hopes for the presence of a child to become the next generation who upholds and maintains the dignity and good name of the family. Every child born into the world is pure, but the marital status of the parents greatly influences the child's legal position. Whether or not the parents' marriage is valid will have an impact on whether or not the child's status is valid in the eyes of the law. Children born in marriages that are not legally valid are called illegitimate children. According to Article 43 paragraph (1) of Law Number 1 of 1974, illegitimate children only have a civil relationship with their mother and their mother's family, but after the issuance of Constitutional Court Decision Number 46/PUU-VIII/2010, illegitimate children can have a civil relationship with father if it can be proven by science and technology or other evidence that he is related to his father by blood. According to Islam, illegitimate children cannot be given inheritance rights, so to ensure their life in the future after the death of their parents, they must be anticipated by making a mandatory will which will come into effect when the person making the will dies. Even though they have received legal recognition through the court, according to Islamic law, illegitimate children do not have inheritance rights, so to ensure the life of illegitimate children, their biological father can provide their inheritance through a mandatory will, the portion of which is according to the provisions of article 209 KHI, namely not exceeding 1/3 of his biological father's inheritance. Keywords: illegitimate children; Treasure; Will; Inheritance.